Maxillary canine with two root canals - Nizar Mohammed Ahmed Mohammed; Ayman O Mandorah; Tahani A Alqashqari (Wolters Kluwer Medknow Publications, 2015)
Inability to find and manage an extra canal (s) is an important cause forfailure of root canal treatment. So, for effective and successful endodontic therapy, root canal morphology and variations should be considered. The purpose of this case report is to present a case of a 58-year-old Saudi male patient with anatomical variations in permanent maxillary left canine in which there is an additional canal (type II of Vertucci classification) was located and treated.